Assessment of Awareness on Climate Change among Public and Private Universities of Lahore - Ayesha Mohsin; Abeera Shehzad; Fatima Bilal; Fatima Imran; Sana Akhtar; Syeda Anna Fatima (CV. Literasi Indonesia, 2022)
As everything in this world evolves or changes, so does our climate. Scientists have now proved that climate change is happening at a much faster rate than before. Pakistan is one of the most vulnerable continents to climate change impacts. Pakistan is considered as 7th most vulnerable country to climate change. Recently in Lahore, many major events occurred due to climate change like the occurrence of smog. The present study was conducted in 4 different tertiary institutions of Lahore, Pakistan. A descriptive survey design was specially employed for this study which used a stratified random sampling method for selecting the students. Moreover, a structured questionnaire titled climate change awareness was developed for collecting data from the students based on their level of awareness. According to this survey, 49.1% of the students know about the policies government is making regarding climate change. 62.5% of the respondents agreed that they have the necessary information to prepare for the impacts of climate change. The result of the findings showed a moderate level of awareness about climate change among the students. Awareness of climate change is an important ingredient for the successful implementation of climate change policy in the country. By improving the climate services and raising awareness about climate change and once it starts to grow it can be integrated into local, national, and sectoral development plans.